An enrichment of rare variants and the lysosomal pathways are important contributors to early onset Alzheimer disease. (December 2021) - Fernandez, Victoria; Pottier, Cyril P; Budde, John P.; Wang, Fengxian; Norton, Joanne; Gentsch, Jen; Morris, John C.; Goate, Alison M.; Beecham, Gary W.; Reitz, Christiane; Ertekin‐Taner, Nilufer; Dickson, Dennis W; et al.
Abstract: Background: A limited number of studies have looked at the genetics of early onset (≤65 years old) Alzheimer disease (EOAD); hence, there is much unidentified heritability contributing to this form of the disease. This study aims to identify novel genes associated with EOAD risk and investigate its differences compared to late onset AD (LOAD). Method: We have combined five cohorts (Knight‐ADRC, NIA‐LOAD, Cache County, Mayo Clinic and ADSP) to generate the largest to date whole exome sequence (WES) non‐Hispanic white EOAD dataset (1, 385 cases and 3, 867 controls). Sequence data was aligned against GRCh37 reference genome using BWA and GATKv3.5 was used to perform variant calling and QC. Statistical analyses included single variant, gene‐based association of rare (MAF<1%) and pathogenic (CADD>20) variants, and pathway analyses. Result: We found that EOAD is enriched in rare nonsynonymous variants compared to LOAD cases (OR=5.67, p=2.2×10 ‐16 ). We identified novel associations ( HOXA1 ‐ OR=2.11, p=4.60×10 ‐14, ADAM29 ‐ OR=6.77, p=2.58×10 ‐08, DHX16 OR=1.65, p=3.18×10 ‐08, ) and a higher effect of certain variants ( TREM2 p.Arg47His, OR=7.28, p=2.02×10 ‐09 ) in EOAD compared to previous LOAD studies (OR=2.08‐4.07). We identified nine statistically significant (p<0.5×10 ‐04 ) genes ( SMG5, BCAM, KCNJ1, UBXN6, MIEN1, FRMPD1, ABCD2, ADAT2 and HADHB ) in both the MAF<1% and CADD>20 gene‐based analysis. These genes are involved in fatty‐acid metabolic processes (pval=2.18×10 ‐04 ) and in endosome to lysosome transport (p=0.003) and we highlight UBXN6, a known Inclusion Body Myopathy with Paget Disease of Bone and Frontotemporal Dementia gene. Conclusion: We are currently performing replication and meta‐analysis to validate these new signals.